microRNA-218 suppresses the proliferation, invasion and promotes apoptosis of pancreatic cancer cells by targeting HMGB1 - Liu, Zhe (Chin J Cancer Res, 2015)
OBJECTIVE: To detect the expression profiles of microRNA-218 (miR-218) in human pancreatic cancer tissue (PCT) and cells and their effects on the biological features of human pancreatic cancer cell line PANC-1 and observe the effect of miR-218 on the expression of the target gene high mobility group box 1 (HMGB1), with an attempt to provide new treatment methods and strategies for pancreatic cancer. METHODS: The expressions of miR-218 in PCT and normal pancreas tissue as well as in various pancreatic cancer cell lines including AsPC-1, BxPC-3, and PANC-1 were determined with quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). The change of miR-218 expression in PANC-1 cells was detected using qRT-PCT after the transfection of miR-218 mimic for 48 h. Cell Counting Kit-8 (CCK-8) was applied for detecting the effect of miR-218 on the activity of PANC-1 cells. The effects of miR-218 on the proliferation and apoptosis of PANC-1 cells were analyzed using the flow cytometry. The effect of miR-218 on the migration of PANC-1 cells was detected using the Trans-well migration assay. The HMGB1 was found to be a target gene of miR-218 by luciferase reporter assay, and the effect of miR-218 on the expression of HMGB1 protein in cells were determined using Western blotting. RESULTS: As shown by qRT-PCR, the expressions of miR-218 in PCT and in pancreatic cancer cell line significantly decreased when compared with the normal pancreatic tissue (NPT) (P<0.01). Compared with the control group, the miR-218 expression significantly increased in the PANC-1 group after the transfection of miR-218 mimic for 48 h (P<0.01). Growth curve showed that the cell viability significantly dropped after the overexpression of miR-218 in the PANC-1 cells for two days (P<0.05). Flow cytometry showed that the S-phase fraction significantly dropped after the overexpression of miR-218 (P<0.01) and the percentage of apoptotic cells significantly increased (P<0.01). As shown by the Trans-well migration assay, the enhanced miR-218 expression was associated with a significantly lower number of cells that passed through a Transwell chamber (P<0.01). Luciferase reporter assay showed that, compared with the control group, the relative luciferase activity significantly decreased in the miR-218 mimic group (P<0.01). As shown by the Western blotting, compared with the control group, the HMGB1 protein expression significantly decreased in the PANC-1 group after the transfection of miR-218 mimic for 48 h (P<0.01). CONCLUSIONS: The miR-218 expression decreases in human PCT and cell lines. miR-218 can negatively regulate the HMGB1 protein expression and inhibit the proliferation and invasion of pancreatic cancer cells. A treatment strategy by enhancing the miR-218 expression may benefit the patients with pancreatic cancer.